Study on the application of shear-wave elastography to thin-layered media and tubular structure: Finite-element analysis and experiment verification. (14th June 2016) - Jang, Jun-keun; Kondo, Kengo; Namita, Takeshi; Yamakawa, Makoto; Shiina, Tsuyoshi
Abstract: Shear-wave elastography (SWE) enables the noninvasive and quantitative evaluation of the mechanical properties of human soft tissue. Generally, shear-wave velocity ( C S ) can be estimated using the time-of-flight (TOF) method. Young's modulus is then calculated directly from the estimated C S . However, because shear waves in thin-layered media propagate as guided waves, C S cannot be accurately estimated using the conventional TOF method. Leaky Lamb dispersion analysis (LLDA) has recently been proposed to overcome this problem. In this study, we performed both experimental and finite-element (FE) analyses to evaluate the advantages of LLDA over TOF. In FE analysis, we investigated why the conventional TOF is ineffective for thin-layered media. In phantom experiments, C S results estimated using the two methods were compared for 1.5 and 2% agar plates and tube phantoms. Furthermore, it was shown that Lamb waves can be applied to tubular structures by extracting lateral waves traveling in the long axis direction of the tube using a two-dimensional window. Also, the effects of the inner radius and stiffness (or shear wavelength) of the tube on the estimation performance of LLDA were experimentally discussed. In phantom experiments, the results indicated good agreement between LLDA (plate phantoms of 2 mm thickness: 5.0 m/s for 1.5% agar and 7.2 m/s for 2% agar; tube phantoms with 2 mm thickness and 2 mm inner radius: 5.1 m/s for 1.5% agar and 7.0 m/s for 2% agar; tube phantoms with 2 mm thickness and 4 mm inner radius: 5.3 m/s for 1.5% agar and 7.3 m/s for 2% agar) and SWE measurements (bulk phantoms: 5.3 m/s ± 0.27 for 1.5% agar and 7.3 m/s ± 0.54 for 2% agar).